Rethinking public spaces in urban residential neighbourhoods: a case study of traditional and contemporary developments in Misurata, Libya - Abaid, Ibrahim (2018)
Public spaces of a city's neighbourhoods and residential areas are one of the key indicators of urban quality. In Libya, in 2005, the government introduced a redevelopment scheme to provide new homes to the local residents and to build thousands of new housing units around the country. This initiative was to offset the shortage in housing numbers due to the rapid population growth and urbanisation. In 2011, 79% of the country’s population lived in urban areas. This high demand for housing by Libya's citizens drove significant changes to the urban planning composition of the country, particularly the residential areas. The government claims that this new strategy aims to fill the shortage of houses within as short a time as possible. This research focuses on two examples of a typical neighbourhoods as case studies in Misurata City, Libya. It investigates the role of public spaces in the traditional neighbourhoods (TNs) and the governmental neighbourhoods (GNs). It compares the conditions of public spaces in both types of neighbourhoods in terms of physical and intangible qualities and examines the relationship between the residents in terms of social integration and community cohesion. In addition, the researcher examines whether this new strategy has affected the social relationships within the local community or not and assesses the extent of the possible impact on the daily activities of residents. Furthermore, the thesis discusses the extent of interaction among the residents regardless of their age, gender and cultural background.